Use of botulinum toxin for rosacea: a pilot study - Jaqueline Barbeito de Vasconcellos; Isabele Oliveira Santos; Daniela Alves Pereira Antelo (Sociedade Brasileira de Dermatologia (SBD), 2021)
Introduction: Rosacea is a chronic inflammatory skin disease. The intradermal application of botulinum toxin (BT) has been studied as a therapeutic option for patients who struggle to manage flushing and/or persistent facial erythema. There is no standard protocol for BT application in rosacea. Objective: To evaluate the effectiveness of botulinum toxin application on erythematotelan-giectatic rosacea. Methods: Pilot study with case series. We applied intradermal BT in 10 patients with a diagnosis of rosacea and symptoms of persistent erythema and/or facial flushing. Patients received 10 to 15 injections per hemiface (1 unit of onabotulinum BT per injection) and 0 to 5 injections in the nasal region, totaling 25 to 35 units per patient. Results: Seventy-five percent of the patients presented a reduction in flush and erythema intensity. The follow-up time was three months, and no serious adverse events were observed. Conclusions: The therapeutic arsenal to control erythema and facial flushing of rosacea, especially refractory to the usual treatment, should consider the intradermal application of BT type A.